Effects of Osteoporosis Specific Standardized Physical Therapy on Functional Capacity, Bone Mineral Density and Bone Metabolism – a 2-Year Prospective and Randomized Study - Dischereit, G.; Müller-Ladner, U.; Lange, U. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2016)
Purpose: Patients with osteoporosis inherit a high risk for pathologic fractures as consequence from falling due to deficits in coordination, balance, muscle strength and endurance. It is believed that a specific training can avoid these complications. Therefore the effects of osteoporosis specific physiotherapy (OSP) on functional capacity, bone mineral density (BMD) and bone metabolism were evaluated in a real-life long-term setting.Methods: 42 patients with manifest osteoporosis receiving adequate calcium and vitamin D supplementation and bisphosphonate therapy were included. 25 patients underwent OSP once a week (exercise group – EG) and were compared to 17 patients without OSP (control group – CG). Outcome parameters at baseline and after 1 and 2 years included assessments of functional capacity and pain as well as BMD and specific markers of bone metabolism (serum osteocalcin and crosslaps).Results: Functional capacities improved significantly only in the EG, a significant pain reduction occurred only in the EG as well. Furthermore the EG demonstrated a significant increase in BMD of the right femur after 2 years (0.84±0.10 g/cm²) as compared to baseline (0.81±0.12 g/cm²) (p<0.02). Moreover a significant amelioration of bone metabolism could be demonstrated only in the EG.Conclusions: This is the first study to show that standardized osteoporosis-specific physiotherapy once weekly results in significant protective effects on functional capacity, bone mineral density and bone metabolism, which is accompanied by a reduced risk of falling in patients with osteoporosis under adequate osteoprotective medical treatment. It needs to be emphasized that even a once-weekly exercise is sufficient to sustain these positive effects.
Keywords: osteoporosis; bone mineral density; bone metabolism; physical therapy; functional capacity